Kualitas Pengalaman dalam Memoderasi Gaya Hidup, Kesadaran Merek, dan Kualitas Rasa Produk terhadap Niat Beli Ulang Konsumen Air Mineral Ades - Ajeng Diah Putri Anggraini; Surya Bintarti (Journal on Education, 2023)
The purpose of this study was to examine the quality of experience in moderating lifestyle, brand awareness and product taste quality on consumer repurchase intentions for ADES mineral water products. This research was conducted with the boundaries of the Bekasi district community as a population. This research was conducted using quantitative methods. The population in this study was everyone who had bought or consumed ADES mineral water products, so that the nature of the population in this study was non-probability sampling with purposive sampling as the respondent. The number of samples collected was 73 respondents. The collected data was processed using the regression test technique which was processed with the SmartPLS 4.0 application. The results of this study show 1) Consumers who buy Ades brand products feel that Ades mineral water products are in accordance with their lifestyle to meet their needs and maintain health. 2) Brand awareness supports customers to make repeat purchases. 3) Ades products have guaranteed quality so as to encourage customer interest to repurchase Ades mineral water products. 4) The quality of customer experience encourages consumers to repurchase the Ades brand mineral water. 5) The quality of experience can moderate brand awareness of the intention to repurchase Ades mineral water. 6) The quality of experience can moderate the quality of Ades mineral water products so as to support consumers buying back Ades mineral water. This shows that the higher the quality of Ades water products will lead to customer satisfaction which will encourage repurchasing. Lifestyle, brand awareness, and product taste quality on Repurchase Intentions for Ades products is stated to have a positive and significant effect.